Yoga Exercises Have an Effect on Accelerating the Recovery of Diastasis Recti Abdominis Muscles in Postpartum Women - Saraswati, Dewi Febriani; Widaningsih, Neneng; Sofiyanti, Santi; Indrayani, Diyan (Women, Midwives and Midwifery, 2026)
Background: diastasis Recti Abdominis Muscle (DRAM), a condition characterized by the separation of the rectus abdominis muscles along the linea alba, commonly occurs postpartum and may impair quality of life. Yoga has been proposed as a non-invasive intervention to address this issue through core muscle engagement and tissue remodeling. Purpose: this study aims to determine the effectiveness of yoga in accelerating the recovery of diastasis recti abdominis muscle in postpartum women. Methods: this quasi-experimental study employed a non-equivalent control group pretest-posttest design. Forty-eight postpartum women (4–10 days postpartum) were recruited, with 45 meeting the inclusion criteria and divided into intervention and control groups. The intervention group participated in structured yoga sessions (20 minutes/session, 4 times/week for 3 weeks), while the control group received routine postnatal exercise advice. The sampling technique used was simple random sampling. DRAM width was measured using a digital caliper. Data were analyzed using paired and independent t-tests. Results: data were analyzed using paired and independent t-tests. A significant reduction in DRAM was observed in the intervention group, with the mean width decreasing from 29.50 ± 3.39 mm to 9.38 ± 2.62 mm (p = 0.000), while the control group showed only a minor decrease (28.09 ± 3.05 mm to 26.03 ± 2.37 mm). Conclusion: the structured yoga intervention demonstrated consistent results with lower post-intervention variability. Yoga exercise significantly improves DRAM recovery in postpartum women by enhancing abdominal muscle strength and supporting tissue regeneration. Yoga is a safe, effective, and reproducible intervention for postpartum rehabilitation